KOMPARASI USAHATANI PADI ORGANIK METODE SRI DAN KONVENSIONAL DI DESA SUMBERSUKO KECAMATAN OKU TIMUR - Saiful Bahrie (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research is to: (1) To know the amount of income obtained by organic rice farmers SRI method compared with inorganic rice in the same planting season, (2) To find out whether there is a significant income difference between organic rice farmers SRI with rice farmers Conventional in Sumbersuko Village Belitang Subdistrict, (3) To know the obstacles and constraints faced in the application of organic rice farming method of SRI in the research location. This research has been conducted in Sumbersuko Village, Belitang District, East OKU Regency. Site selection was done purposively with the consideration that the villages in which the majority of the population livelihood as a rice farmer and there is the Association of Farmers Group (Gapoktan) Sumber Makmur which some members try organic rice cultivation by not using chemical fertilizers or pesticides by SRI method accordingly Criteria of research plan. The research was conducted in April 2014. The research found that the average of income received by organic SRI farmers was Rp 24,614,286 / ha / MT, the production cost was 13,455,452 / ha / MT so that the income was Rp 11,158. 834 / Ha / MT. The acceptance of conventional rice farmers is 20,920,028 / ha / MT, production cost of 11,776,550 / ha / MT so as to obtain revenue amounting to Rp 9,143,478 / ha / MT. The R / C ratio of GKP of SRI Organic farmers is 1.83 and conventional farmers is 1.78. The R / C ratio of rice for SRI Organic farmers is 2.32 and Conventional farmers is 1.87. Statistically there is a significant (significant) difference between the income of organic rice farming SRI and conventional methods. This can be seen from the value of t arithmetic of 8.86 and t table value is 2.055. Value t arithmetic> Value t table so there are significant differences. Obstacles and obstacles of application of organic rice cultivation SRI method in the study sites are: Farmers difficulty in applying SRI rice cultivation technology, Farmers difficulty finding labor or SRI planting workers, Farmers still happy in chemical fertilizers (Minded chemical fertilizers), more organic rice productivity Lower than conventional rice and organic rice marketing is still limited to certain circles.